A New Approach In Direct Shear Testing to Obtain the “True' Residual Properties of Rock Joints - R. O. Roko; G. S. Adisoma; J. J. K. Daemen (Society for Mining, Metallurgy & Exploration, 1986)
A common assumption in determining the shear strength of a rock joint using a direct shear test is that the surfaces undergoing relative shear are in complete contact. Furthermore, the limiting displacement associated with the residual strength values is obtained based on engineering judgement through visual inspection of shear force versus displacement curves. This study proposes a systematic way of determining the residual shear strength of rock joints by evaluating the limiting displacement leading to a minimum cohesive strength value and taking the true area of contact into account. The results of the study indicate that there is a limiting displacement associated with the residual shear strength, and some rocks may have an inherent interface residual cohesive strength different from zero. When the cohesion is different from zero, the residual shear strength is likely to be underestimated if the true area of contact is not considered. In the case where zero calculated cohesion is obtained, the area of contact has no bearing on the shear strength equation because the frictional force depends only on the normal load.